THE EFFECT OF THE PROPORTION OF THE INDEPENDENT BOARD OF COMMISSIONERS, BOARD OF AUDIT COMMITTEES, MANAGERIAL OWNERSHIP AND FREE CASH FLOW ON FINANCIAL PERFORMANCE IN BANKED COMPANIES IN IDX IN 2015-2017 - I WAYAN SUARJANA; NI PUTU ANDHIKA CANDRA DEVI (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study is (1) to determine the effect of the Independent Board of Commissioners Proportion on financial performance in banking companies listed on the Stock Exchange in 2015-2017, (2) to determine the influence of the Audit Committee on financial performance in banking companies listed on the IDX in 2015-2017, (3) to determine the effect of Managerial Ownership on financial performance of banking companies listed on the Stock Exchange in 2015-2017, (4) to determine the effect of Free Cash Flow on financial performance in banking companies listed on the IDX on year 2015-2017. The data needed in this study are financial statements and data on the implementation of Good Corporate Governance. The data is quantitative data obtained by analyzing data through measuring research variables with numbers and statistical procedures. The analysis technique used is multiple linear regression analysis. The sample in this study were 13 banking companies listed on the Indonesia Stock Exchange in 2015-2017. Determination of samples using purposive sampling method. The results showed that the variable proportion of independent board and audit committee had a positive effect on financial performance as indicated by their respective significance values of 0.05. However, managerial ownership and free cash flow variables have no influence on financial performance.